MULTICULTURAL-BASED MANAGEMENT OF CULTURING TOLERANCE VALUES IN ELEMENTARY SCHOOL - Suryaman, Suryaman; Suharyanto, Suharyanto (Jurnal Aplikasi Manajemen, 2022)
Character education is an endeavor that helps help people understand, care about, and act on core ethical values. This study aims to describe the management of teaching tolerance values in elementary schools. The location of this research is SD Pembangunan Jaya 2 Sidoarjo. The research method used is descriptive qualitative research. The result is that through social interaction, students learn to respect other religions so that students have a tolerant attitude. Schools give students the freedom to embrace their respective religions, and they understand the importance of tolerance for students of different ethnicities, races, ethnicities, and religions. Principals instill the values of tolerance by acting as managers, leaders, educators, administrators, and supervisors. Teachers instill values of tolerance through classroom learning, daily activities, examples, suggestions, habituation, and extracurricular activities. The resulting forms of tolerance include: recognizing the rights of everyone, respecting the beliefs of others, do not impose religion on others, living in harmony and peace among human beings, having the spirit of the Pancasila philosophy, and help each other. The findings of this study can be used as input for effective teaching and learning activities in multicultural-based schools. Multicultural-based schools require special attention from the principal because they are prone to conflict. Schools create a conducive climate in transforming the values of tolerance in multicultural-based elementary schools.